(untitled) (Mutah Journal of Humanities and Social Sciences (MJHSS), 2024)
This study aimed at identifying the leadership competencies among the coaches of the first-class clubs from the perspective of the players of table tennis in Jordan. The researcher used the descriptive approach. The study sample consisted of (64) male and female players of those playing in the first class of table tennis sport registered in the official records of the Jordanian Association of Table Tennis for the sports season (2020/2021). The sample was chosen using the intentional technique. The research used a questionnaire that consisted of four domains, the personal and professional competencies, information and sports knowledge competencies, administrative competencies, and communication and interaction competencies, and that involved (29) items. The results showed that the means of the leadership competencies level among the coaches of first-class clubs of table tennis from the perspective of the players were high at the total level. The results revealed that there are no statistically significant differences in the level of leadership competencies among the coaches of first-class clubs of table tennis from the perspective of the players that are attributed to the variables of gender, and years of playing. The study recommends the necessity for first-class clubs to maintain the leadership level of coaches working in table tennis training in Jordanian clubs.